HPLC-DAD Analysis and Investigation of Biological Properties of the Leaves of Globularia alypum (L.), Infusion Extract - Sahar Nouir; Aicha Laouani; Ahmed Loghmari; Khaireddine Bouassida; Raoudha Slim; Rim Bouhajeb; Yosra Hasni; Khaled Saguem; Bouraoui Ouni; Amira Zaïri (MDPI AG, 2023)
Globularia alypum L. (GA) belonging to the Globulariaceae family is a Mediterranean plant which is widely used in traditional Tunisian medicine. The aim of this study was to investigate the phytochemical composition, antioxidant, anti-arthritic, antiproliferative, antibacterial and antibiofilm potential of aqueous GA leaf extracts (AGAL). Quantitative analyses of the different constituents of extracts were evaluated by high-performance liquid chromatography with photodiode-array detection (HPLC-DAD). Spectrophotometric methods and chemical tests were used for antioxidant and anti-arthritic activities. The antiproliferative study was evaluated using colorectal cancer SW620 cells, while the antibacterial assessment and analysis of the antibiofilm effects were determined by the microdilution method and the crystal violet assay, respectively. AGAL extracts presented several components, mainly Nepetin-7-Glucoside and trans-ferrulic acid. The results showed that they had an important antioxidant (IC50 = 0.34; 0.38 and 1.20 mg/mL) and anti-arthritic (IC50 = 2.94 mg/mL) properties, and these effects are displayed in a dose-dependent manner. In addition, this extract demonstrated significant antiproliferative (IC50 = 50 µg/mL), antibacterial (MIC = 6.25 mg/mL and MBC = 6.25 mg/mL), and antibiofilm (59.70% at 25 mg/mL) properties especially against S. aureus. The results achieved confirm the important role of this plant as a source of therapeutic activities.